Comparison of the influence of massive open online courses and traditional teaching methods in medical education in China: A meta‐analysis. Issue 4 (24th April 2021) - Gao, Junwei; Yang, Ling; Zou, Jiao; Fan, Xiaotang
Abstract: In the past 5 years, the MOOC‐based teaching method has been extensively applied as an experimental educational method in medical education in China. However, the effects of this teaching method on medical education are still controversial and ambiguous. To assess the effectiveness of the MOOC‐based teaching method in medical education in China, we conducted the meta‐analysis. Literature search was performed through the PubMed, Embase, Web of Knowledge and CNKI databases through March 3, 2020. Studies evaluating the effectiveness of the MOOC‐based teaching method in medical education in China were included in our meta‐analysis. All data were pooled using a fixed‐ or random‐effect model based on a heterogeneity test. Hedges' g was calculated to evaluate the effectiveness of the MOOC‐based teaching method on the final exam knowledge scores of participants. Subgroup analyses were also carried out. There were 27 studies (25 records) identified in our meta‐analysis. The final exam knowledge scores of participants were statistically higher in the MOOC group compared with the controls in medical courses in China (Hedges' g = 1.080, 95%CI 0.592–1.567, p < 0.001). Obvious heterogeneity across studies was found in the study. Further analysis demonstrated that a significant difference in favor of the MOOC‐based teaching method compared with the traditional teaching method in medical students and doctors. The MOOC‐based teaching method may be applicable to medical education in China, strengthening the roles of MOOCs in medical education.